Exploring changes in individuals travel behaviour after bus Rapid Transit implementation in Dar es Salaam. (April 2022) - Joseph, Lucy; Neven, An; Martens, Karel; Kweka, Opportuna; Wets, Geert; Janssens, Davy
Highlights: This study compares individuals' travel behaviour before and after BRT implementation in Dar es Salaam using a GPS-app to explore possible changes in spatial mobility demands. IPT use remained necessary for low-income individuals to commute to multiple destinations outside the BRT corridor. BRT had become the main option for trips conducted to fixed destinations. Results provide insights for transportation planners who focus mainly on BRT as the solution for all mobility demands. An integrated PT within a framework of a multimode system is important for inclusive mobility. Abstract: The use of Informal Public Transport (IPT; i.e., minibuses, motorcycles, and tricycles) for activity participation in Dar es Salaam is associated with mobility difficulties, e.g., traffic congestion, unscheduled services, and lack of safety of the journey. The introduction of the Bus Rapid Transit (BRT) in May 2016 aimed at reducing mobility difficulties by improving public transport (PT) with scheduled services and fully dedicated lanes to improve access to the Central Business District. This study compares individuals' travel behaviour before and (2 years) after BRT implementation using a GPS-app to explore changes in spatial mobility demands, i.e., (new) visited places, frequency of travel, trip distances, and departure times. Short surveys were used to record the socio-demographic characteristics. Results: the use of IPT remained a necessary means of transport for low-income individuals to commute outside the BRT corridor in multiple destinations, as the use of the BRT route is spatially limited. The new BRT system had become the main option for trips conducted to fixed destinations along the corridor and within service hours. The spatial mobility patterns showed that individuals are now adding BRT to their trip chaining, enabling them to access amenities, make more trips and travel farther distances. The results provide insights for transportation planners who tend to focus mainly on BRT as the only solution for all mobility demands. Each transport system has its own spatial mobility benefits to offer. An integrated PT within a framework of a multimode system is vital for inclusive mobility.